A new enumeration problem of RNA secondary structure - Wang, Wenwen; Zhang, Ming; Wang, Tianming (Utilitas Mathematica, 2008)
In this paper, for the exact enumeration of RNA secondary structures, a new representation of RNA secondary structures is given, which is more meaningful than previous representations. Under the new representation, some recursion formulas for enumerating various types of constrained RNA secondary structures are presented. Furthermore, secondary structures of a given order is discussed.